2013
DOI: 10.1039/c3cs60161g
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2-oxazoline) functionalized surfaces: from modification to application

Abstract: Poly(2-oxazoline)s (POxs) are a versatile class of biocompatible polymers, which have been investigated as poly(ethylene glycol) (PEG) alternatives. In recent years, POxs have drawn significant attention as coatings for antifouling applications. In this tutorial review different approaches to immobilize POxs on surfaces as well as properties and applications of POx coated surfaces will be presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 49 publications
1
95
0
Order By: Relevance
“…[21][22][23][24][25] POxs have generated considerable interest in part because they are able to maintain their antifouling character for longer periods than PEG, suffering less oxidative damage in biological and oxidative media. [21][22][23][24][25] POxs have generated considerable interest in part because they are able to maintain their antifouling character for longer periods than PEG, suffering less oxidative damage in biological and oxidative media.…”
Section: Poly(2-oxazoline)smentioning
confidence: 99%
“…[21][22][23][24][25] POxs have generated considerable interest in part because they are able to maintain their antifouling character for longer periods than PEG, suffering less oxidative damage in biological and oxidative media. [21][22][23][24][25] POxs have generated considerable interest in part because they are able to maintain their antifouling character for longer periods than PEG, suffering less oxidative damage in biological and oxidative media.…”
Section: Poly(2-oxazoline)smentioning
confidence: 99%
“…However, this difference alone is unlikely to explain the differences in the ability of the polymers to support epithelial cells or fibroblasts in the adhesion, motility and growth assays. Our studies demonstrating that polymer-coated glass substrates support cell adhesion conflict with other studies which have 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 shown that PMeOx-coated surfaces inhibited bacterial binding, so-called anti-fouling behaviour [28]. However, in view of the marked differences in the structural properties of bacterial cell walls and mammalian cell membranes, it is not unreasonable to expect differences in binding.…”
Section: Discussionmentioning
confidence: 70%
“…1c. In order to start the sensitization process, as reported in literature [21][22][23], the fiber tips were then immersed into H 2 SO 4 solution maintaining a constant temperature at 80 • C using a hot plate. After H 2 O 2 was added into the H 2 SO 4 solution with a concentration ratio of H 2 SO 4 :H 2 O 2 = 3:1 (also known as the piranha solution) the fiber tip was kept for another 20 min.…”
Section: Sensitization Of Fiber Tipmentioning
confidence: 99%